Aryltetralols from Holostylis reniformis and syntheses of lignan analogous - Pereira, Marcos D.P. [UNESP]; Ferreira, Matheus R. [UNESP]; Messiano, Gisele B. [UNESP]; Cerávolo, Isabela Penna; Lopes, Lucia M.X. [UNESP]; Krettli, Antoniana U. (Elsevier, 2015)
Abstract Two new lignans, an aryltetralol and its methyl ether analogous, were isolated from Holostylis reniformis (Aristolochiaceae) together with futokadsurin C and (-)-8′-epi-aristoligone. The latter was also obtained as an enantiomeric mixture by synthesis and was transformed into aryltetralols and aryltetralenes that were subjected to chiral-HPLC separations. The compound structures were determined by spectroscopic methods. Several of these lignans had their antiplasmodial activity (against Plasmodium falciparum, W2 clone, anti-HRPII) and toxicity to mammalian kidney cells (MDL50) evaluated. (-)-Cyclogalgravin and (-)-aristoligol exhibited activity (IC50 ∼ 10.8 and 8.4 μM, respectively), the latter exhibited lower toxicity.
Keywords: Antiplasmodial activity; Aristolochiaceae; Aryltetralol; Arytetralene; Holostylis reniformis; Lignans